POLITIK TUBUH HOMOSEKSUAL DALAM NOVEL LA MEILLEURE PART DES HOMMES KARYA TRISTAN GARCIA - Pratama, Dian Agustina (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2023)
This study aims to reveal the form of body politics as a political tool against masculine hegemony in Tristan Garcia's novel La Meillure Part des Hommes. This study used descriptive qualitative method and the theory of masculinity to find out the emerging body politics. The results of this study are body politics used by homosexual groups in the novel La Meilleure Part des Hommes in the form of forming homosexual organizations (Stand), campaigns through television, and gay parades to express aspirations.